2021
DOI: 10.1101/2021.12.28.21268440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene-Environment Pathways to Cognitive Intelligence and Psychotic-Like Experiences in Children

Abstract: Identifying the social and biological mechanisms of cognitive and psychological development of children is essential for optimizing preventive and educational efforts. However, the causal pathways by which genetic and environmental factors affect cognitive and psychiatric outcomes remain unknown, especially in early childhood. We examined the causal relationships among genes, the environment, intelligence, and psychotic-like experiences in 7,632 multiethnic (5,905 with European ancestry) children aged 9-10 yea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 145 publications
0
4
1
Order By: Relevance
“…We found that with the presence of residential disadvantage, children more vulnerable to having PLEs when exposed to neighborhood deprivation had lower GPS of cognitive performance and IQ, and higher educational attainment GPS. At first, this finding may seem incongruous with prior reports indicating a negative association between PLEs and educational attainment GPS (28,78,79).…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…We found that with the presence of residential disadvantage, children more vulnerable to having PLEs when exposed to neighborhood deprivation had lower GPS of cognitive performance and IQ, and higher educational attainment GPS. At first, this finding may seem incongruous with prior reports indicating a negative association between PLEs and educational attainment GPS (28,78,79).…”
Section: Discussioncontrasting
confidence: 94%
“…It is plausible that the (heterogeneous) effects of early residential adversity on psychiatric disorders other than prodromal psychosis may not become apparent until later adolescence. Lastly, future research should examine the heterogeneous effects of additional environmental risk factors, such as parenting behavior (28) and early life stress (84), to provide a more comprehensive understanding of the environmental influences on psychopathology.. This study highlights the differential effects of neighborhood disadvantage on intertemporal economic decisions and psychotic risk during early childhood.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations